The effect of pressurized intraperitoneal aerosolized chemotherapy on the surgical treatment outcomes of ovarian cancer with peritoneal carcinomatosis - A. S. Dzasochov; A. A. Kostin; V. L. Astashov; A. B. Turiev; A. D. Uskov; M. A. Andreeva (Исследования и практика в медицине)
The development of new local treatment methods of peritoneal carcinomatosis in ovarian cancer is an urgent task due to the fact that in most cases complete surgical cytoreduction is technically impossible, and systemic cytostatic therapy does not provide a stable therapeutic effect. The pressurized intraperitoneal aerosolized chemotherapy (PIPAC) is a local method of treating peritoneal carcinomatosis in ovarian cancer, which allows for uniform distribution of medicinal aerosol over the peritoneum and is used together with standard combined treatment in order to improve its outcomes.Purpose of the study. To analyze the effect of PIPAC, used in addition to the standard combined treatment of ovarian cancer with peritoneal carcinomatosis, on the clinical outcome of surgical treatment and long-term results.Patients and methods. Our prospective randomized open-label controlled trial included 169 patients with newly diagnosed ovarian cancer with peritoneal carcinomatosis. The main group included 84 patients and 85 in the control group. Randomization was performed intraoperatively using a digital randomizer. The distribution was homogeneous according to the stages of ovarian cancer (Barnard's criterion = 0.292) and the peritoneal carcinomatosis index (PCI) (Mann-Whitney U test = 0.625). We used a combination of surgical cytoreduction with a one-time PIPAC session and subsequent systemic chemotherapy within the framework of one hospitalization, further PIPAC sessions were performed 2 more times with an interval of 42 days in combination with systemic chemotherapy within the framework of one hospitalization. All patients were operated on at the first stage in the volume of extirpation of the uterus with appendages and removal of the large omentum, all underwent systemic cytotoxic therapy scheme: paclitaxeln 175 mg/m2 , carboplatin AUC 5–7) (6 courses with an interval of 21 days). In the main group, 3 sessions of PIPAC were added to the standard treatment. To study the surgical safety profile of PIPAC, all adverse events of a surgical profile were recorded at each hospitalization. The duration of life without relapse was estimated as the main outcome, the median relapse-free survival was the main indicator. The total duration of the study was 36 months.Results. During statistical processing, it was found that the median disease-free survival in the group with the use of PIPAC was 8 months higher. Thus, in the control group, the median disease-free survival was 13 months in the 95 % confidence interval (in the range of values from 12 to 14 months), in the main group – 21 months (95 % confidence interval, range from 18 to 22 months). Surgical adverse events were reported in 1.2 % after 252 sessions of PIPAC over the entire study period. These phenomena didn’t require additional medical interventions, didn’t increase the duration of hospitalization and didn’t lead to the exclusion of patients from the clinical trial protocol.Conclusion. The use of the PIPAC technique as an additional method of standard regional treatment has demonstrated an improvement in the results of treatment of newly diagnosed ovarian cancer with peritoneal carcinomatosis. PIPAC has a favorable surgical safety profile and is a promising method of local exposure to peritoneal carcinomatosis in both clinical and research work.